The Realities of New Soviet Era in Tatar ASSR Village and Their Reflection in National Literature of 1920-30th .......... 317 - Hanipowa, Ilnara I. (Czas w kulturze rosyjskiej, 2019)
THE REALITIES OF NEW SOVIET ERA IN TATAR ASSR VILLAGE AND THEIR REFLECTION IN NATIONAL LITERATURE OF 1920-30THThe article analyzes reflection of socialist innovations of 1920-1930th in works of national literature – Tatar, Mari, Kryashen. On the example of Tatar ASSR village author demonstrates how during the process of establishing Soviet society, the struggle of a new structure with a new morality and old traditions takes place. The transformation of villager world view, his gradual transition from individual to collective consciousness is shown. Considered time as new, Soviet space. A characteristic of time category, associated with the Soviet planned economy – the five-year period is given; local signs of the Soviet time are named.